ESD Ideas: Translating historical extreme weather events into a warmer world - E. Hawkins; G. P. Compo; G. P. Compo; P. D. Sardeshmukh; P. D. Sardeshmukh (Earth System Dynamics, 2023)
A new reanalysis-based approach is proposed to examine how extreme weather events differ in a warmer or cooler counter-factual world. This approach offers a novel way to develop plausible storylines for some types of extreme event that other methods may not be suitable for. As a proof-of-concept, a reanalysis of a severe windstorm that occurred in February 1903 is translated into a warmer world where it produces higher wind speeds and increased rainfall, suggesting that this storm would be more damaging if it occurred today rather than 120 years ago.